NILAI SOSIO-RELIGIUS AJARAN SIWA-BUDDHA DALAM KAKAWIN SUTASOMA KARYA MPU TANTULAR - Ida Bagus Gede Bawa Adnyana; I Kadek Adhi Dwipayana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The “Kekawin Sutasoma” composition is a masterpiece containing the teachings of ethics, philosophy and theological concept of Shiva – Buddha, which guide humans to obtain the essence of ultimate happiness in life. The research on the “Kekawin Sutasoma” composition could be said as the activity and effort to make an inventory of culture, which has the significant objective, namely, protecting and preserving traditions born from the civilization of Hindu – Buddha community. Conducting the research on the “Kekawin Sutasoma” composition composed by Mpu Tantular has signified the digging of the purity of Shiva - Buddha teachings, which become the foundation of the religious life of Hindu people in Bali as well as national and state life. The Shiva – Buddha teachings is the syncretism of Hindu and Buddha religions in Indonesia. During the age of Majapahit Kingdom in Indonesia, the religions of Shiva and Buddha have blended into one and this could be seen in several literary compositions and one of them is “Kekawin Sutasoma”, that educates people to always to get along well with others and living side by side amid differences. In Indonesia, the people consist of different tribes, religions, races and groups and each has its own unique characteristics. If we comprehend Shiva – Buddha teachings in “Kakawin Sutasoma” composition, we are actually taught to get along well amid differences. The purpose is to prevent discord within the Unitary State of the Republic of Indonesia